Nuances of Moh. E. Hasim's Interpretation in the Book of Interpretation of Holy Verses in Reflections - Evarial, Irwan; Azwar, Muhammad (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
The purpose of this study is to examine the nuances of Moh. E. Hasim's interpretation in Tafsir Ayat Suci dalam Renungan (The Holy Verse Interpretation in Reflection), a Sundanese-language exegetical work that displays a contextual, legalistic, and socio-cultural approach. This study uses a qualitative method with a descriptive-analytical approach to the content of the interpretation. The findings show that Hasim's interpretation is characterized by the dominance of fiqh nuances, local socio-cultural influences, the use of popular language, and rational-modern tendencies. He also inserts linguistic elements and scientific theory as a down-to-earth yet critical approach to interpretation. This interpretation reflects the integration of traditional scholarship and contextual reading based on the reality of Sundanese society, while also representing vernacular interpretation that is able to bridge Islamic values with contemporary social needs. His contribution strengthens the repertoire of Nusantara interpretation that is inclusive, responsive, and relevant to the development of the times.